Phenomenology of Ulama and Indonesian Politics - Widia Ningsih; Acep Aripudin (Syntax Idea)
The purpose of this study is to analyze the phenomenon of scholars and politics in Indonesia. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. This research obtained the results that ulama become people who are in the community but are higher in position than leaders. This important position is because the advice, advice and input of scholars' will always be needed by the leader. This is due to the dynamics of Islamic politics, one of which is the transformation carried out by NU youths who were originally pesantren-based into academics and active on campus, The political movement within NU did initially seem reactive which was influenced by the existence of socio-pyolytic conditions on the one hand and external factors that led to the birth of the change process itself.